Simultaneous determination of sunitinib and its two metabolites in plasma of Chinese patients with metastatic renal cell carcinoma by liquid chromatography–tandem mass spectrometry. (28th October 2012) - Qiu, Feng; Bian, Weihua; Li, Jun; Ge, Zhicheng
ABSTRACT A simple and rapid liquid chromatography–tandem mass spectrometry (LC‐MS/MS) method was developed and validated for the simultaneous determination of sunitinib and its two metabolites in plasma of Chinese patients with metastatic renal cell carcinoma (mRCC). After simple one‐step protein precipitation with methanol–acetonitrile (1:1, v/v), all three analytes were separated on an Agilent Zorbax SB‐C18 column using a gradient mobile phase consisting of water (0.1% formic acid)–acetonitrile (0.1% formic acid) at a flow rate of 0.50 mL/min. The detection was performed in multiple reaction monitoring mode, using the transitions of m/z 399.0 → 326.2, m/z 371.0 → 283.1, m/z 343.0 → 283.1 and m/z 386.3 → 122.2 for sunitinib, M1, M2 and buspirone, respectively. The method was linear over the range of 0.10–100 ng/mL for all three analytes using only 50 μL of plasma and the lower limit of quantifications for the three analytes were all 0.10 ng/mL. The intra‐day and inter‐day precisions were all less than 15% and the accuracies were within the range of ±15%; recoveries were between 85.0 and 115%. The validated method was successfully applied to an explorative pharmacokinetic study of sunitinib in Chinese patients with mRCC following multi‐dose oral administration. Copyright © 2012 John Wiley & Sons, Ltd.